Self-care management strategies among individuals living with type 2 diabetes mellitus: nursing interventions - Hunt CW (Dove Medical Press, 2013)
Caralise W HuntAuburn University School of Nursing, Auburn, AL, USAAbstract: Nurses provide care for individuals living with diabetes in a variety of areas. Nursing interventions assist individuals living with diabetes to manage diabetes and can positively affect outcomes. This article describes an integrated literature review conducted to evaluate and summarize nursing interventions and research in self-management of type 2 diabetes mellitus. PubMed, PsycINFO, CINAHL, and the Cochrane database were searched for the years 2002–2013 using the search terms “diabetes”, “type 2 diabetes”, “self-care”, “self-management”, “diabetes self-management”, “intervention”, and “nursing”. Results from the review indicate that nurses deliver care independently and in conjunction with other health care providers for individuals living with diabetes. A majority of the reviewed studies included a nursing education intervention for patients living with diabetes. Nursing interventions are linked to improvements in diabetes knowledge, self-management behaviors, and physiologic and psychologic outcomes.Keywords: type 2 diabetes mellitus, self-care management, nursing interventions